Analisis pengaruh leverage terhadap nilai perusahaan dengan kepemilikan manajerial dan arus kas bebas sebagai variabel pemoderasi - Linawaty, Linawaty; Ekadjaja, Agustin (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
The purpose of this study is to examine whether or not the effect of leverage on firm value with management ownership and free cash flow as moderating variabel practice of manufacture firms listed in Indonesian Stock Exchange for period 2012-2014. Thirty five sample are selected by purposive sampling and used ordinary least square method to analysis. This study used secondary data such as firm financial statement that published during the observation year. Dependent variabel in this study is firm value practice of real estate firms listed in Indonesian Stock Exchange, while the independent variabels are leverage, management ownership, and free cash flow. The result shows that the impact of leverage is significant on firm value; Free Cash Flow is significant moderating leverage on firm, Management Ownership is not significant moderating leverage on firm value